THE EFFECTIVENESS OF ZINC AND RISEDRONATE ON BONE TURNOVER IN RAT MODEL OF OSTEOPOROSIS ASSESSED WITH THE EXPRESSION OF β-CROSSLAPS - Adam Fajar; Mohammad Rizal Chaidir; Dicky Mulyadi; Ahmad Ramdan; Yoyos Dias Ismiarto (Journal Orthopaedi and Traumatology Surabaya, 2018)
Background: Osteoporosis prevalence in Indonesia is high. Risedronate commonly used for treating the osteoporosis. Unfortunately, long term therapy can cause hazardous adverse effect to the patient. Previous research in rat model osteoporosis, Zinc have a potential effect to prevent and rebuild bone structure with osteoblast stimulation in bone formation and osteoclast activity inhibition in bone resorption by increasing Osteoprotegerin production, that inhibit bond between RANKL and RANK.Purpose: To determine the effectiveness of Zink and Risedronate on bone turnover in osteoporotic model rats assessed the β-CrossLaps expression.Methods: This research is conducted as experimental comparative method used 25 female Galur Wistar rat that divided into Non-ovariectomy and Ovariectomy group to induce osteoporosis. The treatment is divided into Zinc-Risedronate, and Zinc, or Risedronate only. One Way Anova and Independent T-test was used to analyzed the significant difference between groups.Result: One Way Anova statistic test forβ-CrossLaps expression value in the 3rd Taken blood sample showed that p is less than 0.05 (p<0.05), which indicated that are significant difference in the mean between variable at 3rd Taken blood sample in all group. Meanwhile, Independent T-test was used to compare β-CrossLaps expression in 3rd taken blood sample between Ovari and Ovari+Zinc, Ovari and Ovari+Zinc+Rise showed p is less than 0.05 (p<0.05), which indicated that there are significant difference in the mean between variable 2 groups.Conclusion: Zinc-Risedronate administration will decrease bone turnover and β-CrossLaps expression more than Zinc or Risedronate only in rat model osteoporosis.